2003
DOI: 10.1152/jn.00388.2003
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Depression Can Be Elicited in Brain Stem of Immature But Not Adult Rats

Abstract: Spreading depression (SD), a neuronal mechanism involved in brain pathophysiology, occurs in brain areas with high neuronal density such as the cerebral cortex. By contrast, the brain stem is thought to be resistant to SD. Here we show that DC shifts resembling cortical SD can be elicited in rat brain stem by topical application of KCl but not by pricking the brain stem. However, this was only possible until postnatal day 13, and, in addition, susceptibility for SD had to be enhanced. The latter was achieved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
26
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 32 publications
9
26
2
3
Order By: Relevance
“…However, it is shown that SD can be elicited in immature rat brainstem by topical application of KCl when the susceptibility for SD enhanced by superfusion of the brainstem with a solution containing acetate instead of chloride ions (Richter et al, 2003). In the present study, SD was elicited relatively easier in the spinal cord.…”
Section: Discussioncontrasting
confidence: 47%
“…However, it is shown that SD can be elicited in immature rat brainstem by topical application of KCl when the susceptibility for SD enhanced by superfusion of the brainstem with a solution containing acetate instead of chloride ions (Richter et al, 2003). In the present study, SD was elicited relatively easier in the spinal cord.…”
Section: Discussioncontrasting
confidence: 47%
“…This is in line with observations in rat hippocampus, where microdialysis with high K + solution ignited series of recurrent SDs (Herreras and Somjen, 1993), and in rat cerebral cortex, where series of SD were observed during spreading ischemia (Windmuller et al, 2005). The relation to an elevated [K + ] e is furthermore underscored by the lack of occurrence of RDs in the immature rat brainstem, where the conditioning superfusate did not contain higher K + concentrations (Richter et al, 2003). However, two observations are noteworthy that suggest differences between mechanisms of KClevoked SD and RDs.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, ␣-chloralose, an anesthetic favored in cerebrovascular studies, may render the cortex more prone to CSD during NMDA superfusion (5,23,26,27,33,34,44,46). Third, the degree of cortical maturation influences CSD susceptibility (20,21,28,41,42,48), and many studies of NMDA-induced vasodilation have traditionally been performed in immature cortex, such as in piglets.…”
Section: Discussionmentioning
confidence: 99%